Production of non-traditional renewable energy in Latin America: economy and public policies - Dalmazzo-Bermejo, Enzo (2017)
The objective of this study is to determine the variables that influenced the development or production of non-traditional renewable energies in Latin America over the period 1995-2007, in order to contribute to the orientation of public policies that promote such production. To this end, we use pool panel and static and dynamic panel data to estimate the factors that influence renewable energy production across 13 Latin American countries. The study identifies the best estimation of the phenomenon, whereby it is the dynamic data panel method that enables the best adaptation to the Latin American reality and orientation of public policies to increased energy production. This study allows a comparison of the results obtained by Dalmazzo-Bermejo and Valenzuela-Klagges (2016), which focuses on a longer period in which behavior subsequent to the subprime crisis is modeled.